A fast and safe technique for sperm preparation in ICSI treatments within a randomized controlled trial (RCT) - Domenico Baldini; Annamaria Baldini; Erica Silvestris; Giovanni Vizziello; Daniele Ferri; Damiano Vizziello (BMC, 2020)
Abstract Recently a novel method based on horizontal sperm migration in injection dishes has been introduced as an additional tool for preparation of semen sample in assisted reproductive technology (ART) procedures. In the present study, we evaluated both timing and reproductive outcomes in a randomized controlled study including 1034 intra-cytoplasmic sperm injection (ICSI) procedures followed by fresh embryo transfer. Couples enrolled were divided into two sub-groups, namely conventional swim-up method (Group A), and horizontal sperm migration in injection dishes (Group B). No significant differences were found between groups with respect to fertilization rate, implantation success, clinical pregnancy outcomes and ongoing pregnancies. On the contrary, both cleavage and blastocyst rates were statistically higher in Group B, suggesting superior efficiency and safety of this innovative technique also including time-saving and cheaper costs as compared to the classical swim-up sperm preparation. Our data support the interpretation of the horizontal sperm migration as a promising procedure for semen preparation in ART cycles.